National survey on total-body irradiation prior to reduced-intensity stem cell transplantation in Japan: The Japanese Radiation Oncology Study Group. (24th May 2019) - Kawaguchi, Hiroki; Soejima, Toshinori; Ishibashi, Naoya; Akiba, Takeshi; Hasegawa, Masatoshi; Isobe, Kouichi; Ito, Hitoshi; Imai, Michiko; Ejima, Yasuo; Hata, Masaharu; Sasai, Keisuke; Shimoda, Emiko; et al.
Abstract: Reduced-intensity stem cell transplantation (RIST) minimizes the adverse effects of traditional hematopoietic stem cell transplantation, and low-dose total-body irradiation (TBI) is administered over a short period prior to RIST (TBI–RIST). Different institutes adopt different approaches for the administration of TBI–RIST, and since no study had previously investigated this issue, a survey of the TBI schedules in Japan was conducted. In October 2015, the Japanese Radiation Oncology Study Group initiated a national survey of TBI–RIST procedures conducted between 2010 and 2014. Of 186 institutions performing TBI, 90 (48%) responded to the survey, 78 of which performed TBI–RIST. Of 2488 patients who underwent TBI for malignant disease at these institutions, 1412 (56.8%) patients were treated for leukemia, 477 (19.2%) for malignant lymphoma, 453 (18.2) for myelodysplastic syndrome, 44 (1.8%) for multiple myeloma, and 102 (4.1%) for other malignant diseases. Further, 206 (52.0%) of 396 patients (a high proportion of patients) who underwent TBI for benign disease had aplastic anemia. The TBI–RIST equipment and treatment methods were similar to those used for myeloablative regimens. Routinely shielded organs included the lungs (43.6%), eyes (50.0%) and kidneys (10.2%). The ovaries (14.1%), thyroid (6.4%) and testicles (16.7%) were also frequently shielded, possibly reflecting an emphasis on shielding reproductive organs in children. TBI–RIST was performed more frequently than myeloablative conditioning in patients with benign disease. Genital and thyroid shielding were applied more frequently in patients treated with TBI–RIST than in patients treated with myeloablative conditioning. In conclusion, this study indicates the status of TBI–RIST in Japan and can assist future efforts to standardize TBI–RIST treatment methods and to design a future multicenter collaborative research study.